Radiofrequency Catheter Ablation of Supraventicular Tachycardias in Nepal - KC, Man Bahadur; Rajbhandari, Sujeeb; Raut, Roshan (Nepalese Heart Journal, 2008)
Shahid Gangalal National Heart Center (SGNHC) is the first and the only one facility providing electrophysiological studies (EPS) and radiofrequency catheter ablation (RFCA) for supraventricular tachycardia in Nepal. The first RFCA for SVT in Nepal was performed on 13th October 2003 with Portable EP lab (EP Tracer-Johnson & Johnson). To date, total of 248 RFCA procedures have been performed in SGNHC. The retrospective analysis of this patients population has provided an opportunity to narrate our initial experience regarding baseline characteristics, EP findings, immediate and follow up outcomes and complications.